User-Centered Design Approach in Developing User Interface and User Experience of Sculptify Mobile Application - Dananjaya, Md. Wira Putra; Prathama, Gede Humaswara; Darmaastawan, Kadek (Information Technology and Science (ITScience), 2024)
In the increasingly digital era, user interface (UI) and user experience (UX) design have become crucial factors in application development. The success of an application is not only determined by its functionality, but also by how well users can interact with the application. User Centered Design (UCD) is an approach that places users as the main focus in every stage of design, from initial research to final evaluation, to ensure that the resulting product truly meets user needs and expectations. This study applies the UCD approach to the UI and UX design of the Sculptify application, which is designed to facilitate the buying and selling of sculptures and other three-dimensional works of art. Given the complexity and uniqueness of art product transactions, effective UI and UX design is very important. This study involves the active participation of potential users through methods such as interviews, surveys, and usability testing to create an intuitive interface and provide a satisfying experience for users. The research stage begins with research to understand user needs and preferences, followed by initial design and a series of tests and iterations based on user feedback. The final evaluation is carried out to measure the extent to which the final design meets user needs and expectations. The results of the UCD implementation are expected to provide valuable insights into the importance of placing users at the center of the design process and how this can improve the quality of interactions and overall user satisfaction.